Radiologic Predictors of Failure of Patellofemoral Instability Surgery in Adolescents. Issue 5 (31st May 2022) - Wilson, Benjamin R.; Zheng, Evan T.; Cook, Danielle L.; Hussain, Zaamin B.; Nunally, Kianna D.; Heyworth, Benton E.; Micheli, Lyle J.; Yen, Yi-Meng; Kramer, Dennis E.; Kocher, Mininder S.
Background: Adolescents often benefit from surgical management of recurrent patellofemoral instability (PFI). However, the precise radiologic risk factors for failure of PFI surgery remains incompletely investigated. Hypothesis/Purpose: The purpose of this study was to determine the rate of failure, defined as recurrence of instability, in a large cohort of adolescent athletes undergoing primary surgery for PFI, and to identify preoperative radiologic risk factors for recurrence. Methods: A retrospective review was performed on patients aged ≤19 years who underwent primary surgery for PFI at a single tertiary care center between 2008 and 2017. Patients underwent procedures including medial retinacular plication/reefing/advancement (MRP), medial patellofemoral ligament reconstruction (MPFLR), tibial tubercle osteotomy with or without MRP (TTO), or combined TTO/MPFLR. Exclusion criteria were BMI >30kg/m 2, surgery for fixation of chondral fractures >1cm, and diagnosis of a syndromic disorder. Preoperative magnetic resonance imaging (MRI) studies were reviewed, and radiologic parameters were recorded. Demographic and radiologic variables were compared between patients with and without subsequent PFI. Logistic regression was utilized to determine which imaging variables were associated with post-operative PFI. Results: 303 patients (mean age 15.1 years, 71% female) underwent surgery for PFI with median follow up time of 3.0 years. At final follow-up, 76/303 (25%) of patients experienced post-operative PFI, with 41 of these patients (54%; 14% overall) undergoing revision PFI surgery. Post-operative PFI patients were younger (14.3 vs 15.4 years; p<0.001) and more likely to have undergone isolated MRP surgery (66% vs 35%; p<0.001) (Table 1). Pertinent radiologic findings in recurrent PFI patients vs non-recurrence patients included open physes (62% vs 49%; p<0.001), larger sulcus angle (163.9 vs 159.2; p<0.001), larger patellar tilt angle (26.3 vs 23.6; p=0.04), and larger Caton-Deschamps Index (CDI) (1.3 vs 1.2; p=0.03) (Table 2). Each additional degree of sulcus angle increased the odds of recurrent instability by 5% (OR=1.05; p=0.002), while each additional year of age decreased the odds of failure by 23% (OR=0.77; p<0.001). Conclusion: In conclusion, 25% of adolescents experienced post-operative PFI after primary patellofemoral stabilization surgery. However, such patients were more likely to be younger—a known risk factor for recurrence—and were more likely to undergo MRP, a procedure now largely replaced by MPFLR. Radiologic risk factors for failure included open physes, flatter trochlea, greater patellar tilt, and greater patella alta. Such data should guide treatment decisions and inform the risk of failure of surgical stabilization procedures in adolescents with PFI. Table 1. Patient Demographics by Presence or Absence of Recurrent Instability (N=303). Table 2. Imaging Measurements by Presence or Absence of Recurrent Instability (N=303).